Development and Clinical Validation of Multiple Cross Displacement Amplification Combined With Nanoparticles-Based Biosensor for Detection of Mycobacterium tuberculosis: Preliminary Results - Jiao, Wei-Wei; Wang, Yi; Wang, Gui-Rong; Wang, Ya-Cui; Xiao, Jing; Sun, Lin; Li, Jie-Qiong; Wen, Shu-An; Zhang, Ting-Ting; Ma, Qi; Huang, Hai-Rong; Shen, A-Dong (Frontiers in Microbiology, 2019)
Tuberculosis is still a major threat to global public health. In the present study, multiple cross displacement amplification was combined with nanoparticle-based lateral flow biosensor (MCDA-LFB) to detect IS6110 and IS1081 simultaneously of Mycobacterium tuberculosis (MTB) in DNA extracts of reference strain H37Rv and clinical samples. The amplification can be finished within 30 min at a fixed temperature (67ºC). The limit of detection of multiplex MCDA assay was 10 fg per reaction. By using the multiplex MCDA protocol, cross-reaction with non-mycobacteria and NTM strains was not observed. Among clinically diagnosed TB patients, the sensitivity of liquid culture, Xpert MTB/RIF and multiplex MCDA assay was 42.0% (50/119), 49.6% (59/119) and 88.2% (105/119), respectively. Among culture positive samples, the sensitivity of Xpert MTB/RIF and multiplex MCDA assay was 86.0% (43/50) and 98.0% (49/50), respectively. Among culture negative samples, the sensitivity of Xpert MTB/RIF and multiplex MCDA assay was 23.2% (16/69) and 81.2% (56/69), respectively. The specificity was 100% (60/60) for Xpert MTB/RIF and 98.3% (59/60) for multiplex MDCA. Therefore, the multiplex MCDA assay for MTB detection is rapid, sensitive and easy to be used. It is promising for early diagnosis of TB.